The Psychometric Properties of the Norwegian version of Ages & Stages Questionnaire: Social and Emotional, ASQ:SE - Rasmussen, Lene-Mari P.; Martinussen, Monica (PsykTestBarn, 2013)
Description: Ages & Stages Questionnaire: Social and Emotional (ASQ:SE) is a screening tool for assessing social and emotional difficulties in babies and young children (Squires, Bricker & Twombly, 2003). The test was translated to Norwegian in 2007 by Harald Janson, Torill Ueland, and Vibeke Kennair Ottesen at the Center for child and Adolescent Mental Health, Eastern and Southern Norway (RBUP). Currently, the Norwegian version of ASQ:SE is being piloted by RBUP and is not publicly available. ASQ:SE is a questionnaire to be completed by parents, and there are different versions for different age groups and developmental levels. There are eight different versions with between 19 and 33 questions per questionnaire which are combined to seven scales. The test may be used for children from 3 to 66 months. It takes between 10 and 15 minutes for the parents to complete the test, and the scoring takes 2-3 minutes for the test administrator. The test may be used for both clinical and research purposes. Relevant education and training is required in order to use the test. Literature search: The search resulted in one Norwegian article and four Swedish articles that fulfilled the inclusion criteria. Psychometrics: There were no Norwegian studies reporting psychometric results for the test. One study reported mean total score for a clinical sample (preterm babies). The Swedish study reported comparisons between ASQ:SE and psychological stress among mothers and observations of mother-baby interactions. The results indicated some problems with using the test in clinical samples of mothers. Conclusion: There is a need for studies examining the psychometric properties of the test in addition to norms with cut-off values for clinical use.